Minimal Intervention Approach for Complicated Crown- root Fracture using Reattachment procedure: Three Years Follow-up - Shrestha, Sita; Vikram, Mannu; Singh, Ripu; Bantawa, Shikha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Crown-root fractures are commonly encountered in dental practice, and their management poses a challenge to clinicians. With the advent in adhesive dentistry, reattachment of the fractured segment became a viable restorative alternative. Reattachment is a conservative treatment option that allows for immediate restoration of function, esthetics and phonetics. This case report presents a minimal intervention approach to the management of a complicated crown root fracture. The tooth was endodontically treated followed by esthetic reattachment of the fractured fragment using composite fiber post. The patient was followed up for three years, and clinical and radiographic examinations showed a successful treatment outcome.